The effectiveness of the realistic math education (RME) learning method based on manipulative media in improving the problem-solving abilities of elementary school students - Ufi Puspita Sari Umar; Zakaria Zakaria (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
This study aims to determine the profile of students' mathematical problem solving abilities before and after being taught using the Manipulative Media-Based Realistic Mathematic Education (RME) method, the effectiveness of the Manipulative Media-Based Realistic Mathematic Education (RME) method in improving students' mathematical problem solving abilities, and differences in solving abilities students' mathematical problems between before and after the application of the Realistic Mathematical Education (RME) learning method. This research is a quantitative pre-experimental design. The research design used is the One Group Pretest-Posttest Design pattern. This design has a pretest, before being given treatment. The data collection technique in this study used a multiple-choice test technique. The data in this study were analyzed using descriptive and inferential statistical analysis techniques. The results of this study indicate that the problem-solving abilities of students before being taught the Realistic Mathematics Education (RME) method based on manipulative media have an average value of 35.00, a standard deviation of 15.022 with a completeness percentage of 8% and after applying the Realistic Mathematical Education method ( RME) based on manipulative media students' problem solving abilities have an average of 84.20, a standard deviation of 8.602 with a completeness percentage of 92%; learning using the Realistic Mathematical Education (RME) method based on manipulative media is effective in improving students' problem solving abilities in mathematics; and there are differences between before and after the implementation of the Realistic Mathematical Education (RME) method based on manipulative media.